2021
DOI: 10.7324/jhsr.2021.623
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Inflammatory Indices in Hospitalized Nigerian COVID-19 Patients

Abstract: The pandemicity of coronavirus disease 2019 (COVID-19) necessitated its novel biomarkers in prognosis and monitoring in low resource settings. Changes in total white blood cell counts have been associated with the progression of diseases. This study determined the prognostic value of some cellular inflammatory cells and their indices in relation to duration of hospital admission, gender, and age of COVID-19 patients. This longitudinal and case–control study determined blood cell components (total white blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…As recently documented by Kuluöztürk, the Glasgow prognostic score also has been observed to correlate with COVID-19 infection severity and worse outcome among Turkish patients [22]. The current data presented in this study corroborates the widely observed pathophysiologic basis of COVID-19 severity and underscore the role played by hyper-inflammation in the disease evolution and progression [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Relationship With Existing Literaturesupporting
confidence: 86%
See 2 more Smart Citations
“…As recently documented by Kuluöztürk, the Glasgow prognostic score also has been observed to correlate with COVID-19 infection severity and worse outcome among Turkish patients [22]. The current data presented in this study corroborates the widely observed pathophysiologic basis of COVID-19 severity and underscore the role played by hyper-inflammation in the disease evolution and progression [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Relationship With Existing Literaturesupporting
confidence: 86%
“…In another study reported by Iqbal and colleagues among Indian COVID-19 patients with a relatively large sample size population (n=433) compared to that of Alam and colleagues, the authors found elevated pro-inflammatory markers including CRP among the severely ill patients and they concluded that the pro-inflammatory markers be used to differentiate severe from non-severe patients with COVID-19 infection [7]. Similar findings have been documented in two previous Nigerian studies [12,16].…”
Section: Relationship With Existing Literaturesupporting
confidence: 66%
See 1 more Smart Citation
“…3,10 Leukopenia, leukocytosis, neutropenia and lymphopenia are among the most common laboratory abnormalities in COVID-19. 13,14 Tan et al showed that lymphocyte percentage was inversely related to the severity and prognosis of COVID-19 patients. 13 Although, reports on haemocytometric changes in COVID-19 infection at different stages of the disease are many, the roles of these changes in indicating disease prognostication is still poorly understood especially, in Nigerian COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreso, repurposed medication used for COVID-19 patients at IDC, Ibadan, Nigeria are combinations of vitamin D, vitamin C, Zn, azithromycin, hydroxychloroquine and chloroquine (as an alternative to hydroxychloroquine). 14,[16][17][18][19][20] The treatment options for COVID-19 at this center are largely supportive as there is no universally agreed protocol of care. In addition, these medications were not used in the context of a trial but the positive outcomes encouraged their continued use.…”
Section: Introductionmentioning
confidence: 99%